γ2 GABAAR Trafficking and the Consequences of Human Genetic Variation - Lorenz-Guertin, Joshua M.; Bambino, Matthew J.; Jacob, Tija C. (Frontiers in Cellular Neuroscience, 2018)
GABA type A receptors (GABAARs) mediate the majority of fast inhibitory neurotransmission in the central nervous system (CNS). Most prevalent as heteropentamers composed of two α, two β, and a γ2 subunit, these ligand‐gated ionotropic chloride channels are capable of extensive genetic diversity (α1‐6, β1‐3, γ1‐3, δ, ε, θ, π, ρ1‐3). Part of this selective GABAAR assembly arises from the critical role for γ2 in maintaining synaptic receptor localization and function. Accordingly, mutations in this subunit account for over half of the known epilepsy-associated genetic anomalies identified in GABAARs. Fundamental structure-function studies and cellular pathology investigations have revealed dynamic GABAAR trafficking and synaptic scaffolding as critical regulators of GABAergic inhibition. Here, we introduce in vitro and in vivo findings regarding the specific role of the γ2 subunit in receptor trafficking. We then examine γ2 subunit human genetic variation and assess disease related phenotypes and the potential role of altered GABAAR trafficking. Finally, we discuss new-age imaging techniques and their potential to provide novel insight into critical regulatory mechanisms of GABAAR function.